The Impact of the Rs1044457 Polymorphism in the CMPK1 Gene on the Response Rate to Gemcitabine‐Based Chemotherapy in Metastatic NSCLC Patients - Ghassan Saod Saleh; Fouad Kadhim Gatea; Qasim Sharhan Al‐Mayah; Hayder Lazim (Advanced Genetics)
Abstract This study aims to evaluate the role of a specific gene polymorphism, Cytidine/Uridine Monophosphate Kinase 1 (CMPK1) rs1044457, in predicting the response to gemcitabine‐based chemotherapy in patients with NSCLC. A total of 98 NSCLC patients are enrolled in the study. Based on their response, patients are classified as either responders or non‐responders. Specific primers are designed to amplify the rs1044457 variant and performed genotyping using restriction fragment length polymorphism (RFLP). The rs1044457 variant showed a statistically significant difference in frequency between responder and non‐responder patients. The mutant genotype (TT) is more frequent in non‐responder patients (18.75%) compared to responder patients (4%), with an odds ratio [OR] of 5.93 (95% confidence interval [CI] = 1.16–30.25, p = 0.032). Additionally, at the allelic level, the mutant allele (T) is more common in non‐responder patients (36.46%) compared to responder patients (23%), with a statistically significant odds ratio of 1.92 (95% CI = 1.03–3.58, p = 0.040). The findings of this study suggest that the mutant allele (allele T) of the rs1044457 variant may serve as a risk factor for resistance to gemcitabine‐based chemotherapy in patients with NSCLC.